Sectoral labor income share dynamics: Cross-country evidence from a novel dataset - Yoko Oishi; Saumik Paul (Asian Development Bank Institute (ADBI), 2018)
Despite steady growth of the literature on labor income share, empirical studies are mostly limited to country-level analyses. At the sectoral level, data on labor income share are available only for advanced countries. This paper overcomes this constraint and provides some preliminary outcomes from a novel dataset that the authors compile at the sectoral level (10 sectors) for 53 countries, including 20 developing countries. The preliminary evidence suggests that, at the disaggregated level, the government service sector accounts for the largest share of labor income (46%), whereas public utilities (16%) and mining (20%) are the sectors with the smallest shares of labor income. The unweighted average labor income share in developing countries is slightly lower than that in developed countries. We find considerable variation in labor income share estimates within each region and within each broad category of sectors, measured at the level and with changes over time.
Keywords: E24; E25; J30; 330; labor income share; cross-country data; income distribution